Influence of proactive, networking and resourceful on entrepreneurial intention and change of life style among asnaf generation Z in Sabah - Siti Nor Bayaah Ahmad; Ikmal Malik; Irma Wani Othman; Salmah Topimin; Haslinda Hasan (Academic Inspired Network, 2022)
It is the objective of this study is to identify the characteristics that predict entrepreneurial intention and lifestyle change among Asnaf Generation Z in Sabah, Malaysia. The purpose of this study was to explore the effect of elements based on the theory of planned behaviour, such as proactive, social networking, and resourceful, on the entrepreneurial intention and lifestyle change of Asnaf gen Z. 106 university students from higher learning institution in Sabah participated in the online survey that is used for the study. PLS-SEM, or partial least squares structural equation modelling, was utilised to analyse the data. The results suggested that social networking and proactive behaviour were significant for Asnaf Gen Z entrepreneurial intention. In addition, the entrepreneurial motivation had a favourable impact on the Asnaf Generation Z's efforts to alter their current lifestyle. As a result, the Asnaf generation Z's aspiration for the future is to be their own boss and operate a viable business.